(untitled) (Nigerian Journal of Technology, 2020)
This study conducts a comparative evaluation the effect of using palm kernel oil (PKO), pure petroleum diesel and their blends (B5, B10, B20, B30, B40, and B100), on the performance of a four-cylinder CI diesel engine (David Brown 990: 58hp; 2WD), at Farm Power and Machinery Test laboratory Centre (FPMTLC), Department of Agricultural and Bioresources Engineering, University of Nigeria, Nsukka. The objective of the study was to determine the fuel consumption rates, energy expended, brake specific fuel consumption, and brake thermal efficiency, under varying operating speeds (700 – 1900rpm) at constant torque. Each fuel test was conducted using the Heenan-Froude hydraulic dynamometer engine-test-bed; pure petroleum diesel (B0) was used to generate the baseline data. Variables calculated were analyzed, then compared with each other to determine the differences in the engine performance and also to determine the optimum test fuel. The results obtained show that B10 had the overall optimum energy output, fuel consumption rates, and brake specific fuel consumption of 5431.809J, 3.42E-07 m3/s, and 0.16569l/KWh, respectively at the highest engine speed of 1900. B10 had an excellent brake thermal efficiency of 60.6% but was not better than B100, which showed a higher value of 66.95%. From the analysis, B10 is the optimum test fuel and can be used as an alternative fuel in David Brown 990 (58hp; 2WD) or similar CI diesel engines without any engine modification, even though B100 showed potential as an alternative to fossil diesel. Biofuel production grows through integrated aquaculture and algae production; the algae oil will serve as a raw material for biofuel production http://dx.doi.org/10.4314/njt.v39i3.15